The Impact of the Science-Technology-Society Model on the Enhancement of Student’s HOTS: A Systematic Literature Review - Khoeriyah, Zahwaty; Novitasari, Aulia; Pratama, Anisa Oktina Sari (Universitas Negeri Semarang, 2025)
The Science Technology Society (STS) model is a contextual approach thatlinks science concepts with social issues to encourage higher order thinkingskills (HOTS). This study aims to systematically review various empiricalstudies related to the application of STS in Biology learning to improvestudents' HOTS at the high school level. The method used is SystematicLiterature Review (SLR) with the PRISMA approach, involving the selectionof 15 articles published in 2015–2025 from Scopus, Sinta, and reputableproceedings. The analysis is focused on publication trends, methodologydesign, implementation context, and its impact on HOTS. The results of thereview show that the application of STS consistently improves analytical (C4),evaluation (C5), and creative (C6) skills, as well as supporting students' scienceprocess skills, scientific attitudes, and active engagement. The majority of thestudies analyzed used quasi-experimental design and learning contexts basedon local environmental, health, and technological issues. Challenges includetime constraints, teacher understanding, and supporting infrastructure.Therefore, intensive teacher training, contextual media development, and STSintegration into the curriculum are needed. This study confirms that STS is arelevant and effective pedagogical approach in supporting HOTS-based 21stcentury learning